2019
DOI: 10.7717/peerj.7716
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of hirudin-HN, a new thrombin inhibitor, from the salivary glands ofHirudo nipponia

Abstract: Transcriptome sequencing data (6.5 Gb) of the salivary glands of the haematophagous leech Hirudo nipponia was obtained by using the BGIseq-500 platform. After identification and analysis, one transcript (Unigene5370) was annotated to hirudin HV3 from Hirudo medicinalis with an e-value of 1e-29 and was named hirudin-HN. This transcript was a new thrombin inhibitor gene belonging to the proteinase inhibitor I14 (hirudin) family. Hirudin-HN, with a 270-bp cDNA, encodes an 89-aa protein containing a 20-aa signal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 66 publications
1
25
1
Order By: Relevance
“…Hirudin deactivates thrombin by simultaneously binding to the active site to form irreversible stoichiometric complexes. 31 qRT-PCR confirmed that the level of miR-24 increased after ICH in ECs, which were isolated by LCM. EC proliferation was also observed.…”
Section: Thrombin Elevated Mir-24 Expression and Angiogenesis After Ichmentioning
confidence: 67%
“…Hirudin deactivates thrombin by simultaneously binding to the active site to form irreversible stoichiometric complexes. 31 qRT-PCR confirmed that the level of miR-24 increased after ICH in ECs, which were isolated by LCM. EC proliferation was also observed.…”
Section: Thrombin Elevated Mir-24 Expression and Angiogenesis After Ichmentioning
confidence: 67%
“…Therefore, coagulation is retarded or completely prevented relying on the hirudin concentration in blood. 11 , 12 In Figure 1 previous research of LSE demonstrated that it contains a wide range of active proteins with diverse molecular weight.…”
Section: Introductionmentioning
confidence: 97%
“…Exploring the diversity of anticoagulant-related proteins and framing these in an evolutionary context in terms of presence or absence of orthologues across the phylogeny of leeches would help evince the general evolution of these proteins. Members of several leech families have been investigated at the transcriptome level for compositions of the anticoagulant repertoires, including members of Piscicolidae, Glossiphoniidae, Macrobdellidae, Haemadipsidae, Praobdellidae and Hirudinidae 3,8,[15][16][17][18][19][20][21][22][23][24] . Genome-level evaluations within a species like H. medicinalis would allow insights into the diversity of bioactive proteins available.…”
mentioning
confidence: 99%